System dynamics approaches to energy policy modelling and simulation. (December 2017) - Mutingi, Michael; Mbohwa, Charles; Kommula, Venkata P.
Abstract: Energy systems are complex dynamic systems that are often associated with uncertain system behavior. System behavior is influenced by several dynamic uncertainties, nonlinear relationships between system variables, time lags, and interactive feedback loops that are inherent in the energy system. In turn, these complexities are a result of the underlying structures of energy systems. Under this climate, it is essential to develop systems analysis approaches that can be used for development and evaluation of energy system policies, both at tactical and strategic levels. The purpose of this research is to present a taxonomic analysis of system dynamics approaches to energy policy modelling and simulation. First, we present an outline of dynamic complexities prevalent in energy systems. Second, we make a taxonomic analysis of energy policy formulation problems, learning from the literature. Third, we provide a causal loop analysis of the generic structures of the identified energy formulation problems. The archetypes presented form a valuable platform for system dynamics simulation of energy policy modelling and simulation.